Solving mathematics problems and working with designed student responses: the role of social metacognitive regulation - Evans, Sheila (2018)
When students work productively together on a mathematical problem they are required to simultaneously manage their own efforts, while understanding what others are doing, and saying. Consequently, it is argued that monitoring and regulating the construction of meaning involves individual metacognitive processes, operating socially. This can take three forms: learners regulate their own cognitive processes; scaffold their partner’s understandings by taking on the role of a tutor; or mutually regulate their joint understanding. Engaging in these ways when solving unstructured non-routine problems can substantially extend students’ understanding and raise levels of achievement as measured by standard assessment criteria. Unfortunately, extant literature suggests that these processes of social metacognitive regulation (SMR) can remain elusive for many students. The aim of this study was to develop an intervention to support students in this endeavour. In so doing, local theory concerning the intervention was established.